Implementation of Muhammadiyah Tarjih Decisions on Fajr Time: A Study of Mosques in Medan - Pratama, Muhammad Roni; Tanjung, Dhiauddin (Jurnal Hukum Magnum Opus, 2025)
The determination of the time of dawn is highly dependent on the position of the sun. The government, through the Ministry of Religious Affairs, has long used a sun depression angle of -20° as a marker of the beginning of dawn. However, the latest decision of the XXXI Tarjih National Conference revised this criterion to -18°. This change directly leads to a shift in the calculation of the time of Fajr, becoming backward in time by 8 minutes. This study was conducted to analyze more deeply the implications of the change in the criteria for determining the time of dawn, which resulted from the national deliberation of Islamic religious experts. Internal and external factors of the implementation of the Muhammadiyah Tarjih decision on the criteria for the beginning of Fajr time in the Muhammadiyah mosque in Medan City. In this case, it is necessary to conduct research that uses clear data analysis, and descriptive-analytical methods to provide answers to existing problems and find conclusions, namely the research conducted produces and that the efforts of the Tarjih and Tajdid Council of Muhammadiyah Medan City to try to implement and socialize to the congregation, Muhammadiyah sympathizers and the surrounding community regarding the Tarjih Decision on the beginning of dawn time have accurate data and can be accounted for.